2013
DOI: 10.1007/s11030-013-9480-8
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and anti-cancer activity of a glycosyl library of $$\varvec{N}$$ N -acetylglucosamine-bearing oleanolic acid

Abstract: N-Acetylglucosamine-bearing triterpenoid saponins (GNTS) were reported to be a unique type of saponins with potent anti-tumor activity. In order to study the structure-activity relationship of GNTS, 24 oleanolic acid saponins with (1 --> 3)-linked, (1 --> 4)-linked, (1 --> 6)-linked N-acetylglucosamine oligosaccharide residues were synthesized in a combinatorial and concise method. The cytotoxicity of these compounds toward the leukemia cell line HL-60 and the colorectal cancer cell line HT-29 could not be imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…After 2 h, the solution was concentrated, and the residue was purified by silica gel column chromatography (petroleum ether-EtOAc, 3:1) to give 15 (237 mg, 86%) as a white solid. R f = 0.33 (petroleum ether-EtOAc, 3 (16). A solution of 15 (200 mg, 0.18 mmol), 4 (365 mg, 0.27 mmol) and pre-activated 4 Å MS in dry CH 2 Cl 2 (20 mL) was stirred for 30 min at room temperature, and then cooled to −30 °C.…”
Section: -O-[2-acetamido-346-tri-o-acetyl-2-deoxy-β-d-glucopyranosmentioning
confidence: 99%
See 1 more Smart Citation
“…After 2 h, the solution was concentrated, and the residue was purified by silica gel column chromatography (petroleum ether-EtOAc, 3:1) to give 15 (237 mg, 86%) as a white solid. R f = 0.33 (petroleum ether-EtOAc, 3 (16). A solution of 15 (200 mg, 0.18 mmol), 4 (365 mg, 0.27 mmol) and pre-activated 4 Å MS in dry CH 2 Cl 2 (20 mL) was stirred for 30 min at room temperature, and then cooled to −30 °C.…”
Section: -O-[2-acetamido-346-tri-o-acetyl-2-deoxy-β-d-glucopyranosmentioning
confidence: 99%
“…15 In addition, a glycosyl library of N-acetylglucosamine-bearing oleanolic acids and a series of N-acyl, N-alkoxycarbonyl, and N-alkylcarbamoyl derivatives of 20-deoxy-glucosyl-bearing oleanolic saponins were designed and synthesized by Liang and coworkers, which were evaluated against HL-60, PC-3, and HT29 tumor cancer cells. 16,17 Recently, Ngadjui and coworkers reported seven novel bidesmosidic triterpenoid saponins, albidosides A-G, isolated from the roots of Acacia albida with cytotoxicity against Hela and HL-60 cells. 18 However, the formidable task of isolating these compounds turned out to be a great obstacle for further pharmacological research, so it is valuable to complete the synthesis of these N-acetylglucosaminebearing bidesmosidic triterpenoid saponins for further structure-activity relationships (SAR) investigations.…”
Section: Introductionmentioning
confidence: 99%
“…There have been several reports on the biologically active glycosides. [36][37][38] Both quercetin 3-␤-glucoside and quercetin 4 -␤glucoside have been reported to show inhibitory action on cancer cell proliferation. 36 Iwadate et al…”
Section: Antioxidant Antiallergic Antiphosphodiesterase Activities mentioning
confidence: 99%
“…37 It has been reported that the N-acetylglucosamine analog of oleanolic acid showed high anticancer activity, which was about three times stronger than that of the aglycone (i.e., oleanolic acid). 38 To clarify the efficiency of glycosylation for the physiological and pharmacological activities of stilbenes, we examined several in vitro bioassays of stilbenes and their glycosides. 27 First, the antioxidant activities of the stilbenes resveratrol (1), resveratrol 3-␤-glucoside (2), resveratrol 4 -␤-glucoside (3), pterostilbene (4), pterostilbene 4 -␤-glucoside (5), piceatannol (6), piceatannol 4 -␤-glucoside (7), resveratrol 3-␤-maltoside (8), and resveratrol 4 -␤maltoside (9) were investigated by a bioassay of their DPPH free radical-scavenging activity in vitro.…”
Section: Antioxidant Antiallergic Antiphosphodiesterase Activities mentioning
confidence: 99%
“…An orthogonal protection scheme was also developed for an oleanoyl glycoside, which was used as an intermediate for the synthesis of saponins. 98 In this strategy, free hydroxyl groups on the glucosamine core were protected with Lev, 2-nitrophenylacetyl (NPAc), and TBDPS groups. Though stepwise synthesis of the orthogonally protected oleanoyl glycoside 132 was not shown, the orthogonality of the strategy was clearly illustrated (Scheme 13).…”
Section: Scheme 10: Orthogonal Protection Of Glucosamine 116mentioning
confidence: 99%